DEVELOPING STUDENTS' SPEAKING ABILITY THROUGH GENRE-BASED TEACHING :Action Research with the First Year Students in a Senior High School - Novianti, Rully Raslina (2011)
This study aims to investigate the students' speaking ability in recount text by using the genre-based approach to teaching speaking in one state senior high school in Subang, West Java. This study uses action research design which employed two data collection techniques, i.e. the documentation of students' speaking ability and questionnaire. The data were analyzed based on the criteria in assessing speaking and also recount text which were validated through triangulation. The study revealed that the students speaking ability improved. Findings indicate that the students' responses towards the approach in speaking class showed positive attitudes. The findings of this study suggest that genre-based approach can help develop students' speaking ability. The stages in genre-based approach can help the students to gain information step by step and then formulate it to construct ideas in written and spoken texts. It was shown in the students' speaking scores that gradually improved from one test to other ones. In addition, the students also gave positive responses towards the implementation of this approach in the class. They had interest to do activities and discuss in groups and also to perform individually in independent construction of text.